Faktor-faktor yang mempengaruhi audit report lag pada perusahaan yang terdaftar di bursa efek Indonesia - Yusrawati Juwita Harahap; Yusrarlaini -; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to obtain empirical evidence about the factors that affect the audit report lag. Factors tested audit report lag is a measure of the company, the firm size, auditor turnover and profitability. The population in this study were 45 blue-chip companies listed in Indonesia Stock Exchange Year 2011-2012. Data were obtained from the blue-chip company's financial statementsin 2011-2012. Based onpurposive sampling method, samples were obtained by 33 companies and 2 years of data are used so that the sample companies to 66 companies. This hypothesis was tested using multiple regression analysis.The results ofthis study indicatethat company size, turnover and profitability auditors significant effect on audit report lag. While the size of the firm no effect on audit report lag.Keywords: Audit report lag, the size of the company, the size of the firm, the change of auditors and auditor turnover.